Infliximab no tratamento da artrite psoriásica grave Infliximab in treatment of severe psoriatic arthritis - Adriano Jaime Consorte Loyola; Lia Cândida Miranda de Castro; Sulamita Costa Wirth Chaibub; Antônio Carlos Ximenes (Sociedade Brasileira de Dermatologia, 2005)
A artrite psoriásica tem sido reconhecida como doença imunomediada, em que há participação de células T produtoras de citocinas (fator de necrose tumoral-alfa). O infliximab é anticorpo monoclonal que se liga e inativa o fator de necrose tumoral-alfa. Relata-se um caso de artrite psoriásica grave, refratária a várias terapêuticas sistêmicas, tratado com infliximab 5mg/kg, em infusão venosa de três horas, nas semanas 0, 2, 6 e 14, associado com baixa dose de metotrexato, que apresentou excelente resposta terapêutica. Psoriatic arthritis has been recognized as an auto-immune disease in which there is participation of the cytokine-producing T cells (tumor necrosis factor-alpha). Infliximab is a monoclonal antibody that binds to and inactivates tumor necrosis factor-alpha. Reported is a case of severe psoriatic arthritis which was unresponsive to multiple systemic therapies and treated with an intravenous infusion of infliximab, 5mg/Kg in three hours, in weeks 0,2,6 and 14, associated with a low dose of methotrexate, with an excellent therapeutical response.